2020
DOI: 10.1186/s40659-020-00287-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the role of the interleukins in colon cancer

Abstract: Background: The role of interleukin family in colon cancer remained controversial. The purpose of this study was to investigate the association between interleukin family and colon cancer progression through bioinformatics methods and to validate such association in clinical patients. Methods: A total of 15 differentially expressed interleukins between the colon cancer tissue and normal colon tissue were evaluated from the Cancer Genome Atlas (TCGA) database with R software and only interleukin-7 (IL-7) was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The coding product of IL7 gene is interleukin-7, and the combination of IL7 and its receptor IL7R is essential for T cells (45). It has been reported that IL7 can inhibit the development of colon cancer, and the level of IL7 in colon cancer samples is signi cantly reduced (10), which is consistent with our results. IL7 may play an anti-tumor role through apoptosis pathway [48]In addition, IL7 can also enhance the anti-tumor immunity by combining other factors to enhance the function of immune cells (46).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The coding product of IL7 gene is interleukin-7, and the combination of IL7 and its receptor IL7R is essential for T cells (45). It has been reported that IL7 can inhibit the development of colon cancer, and the level of IL7 in colon cancer samples is signi cantly reduced (10), which is consistent with our results. IL7 may play an anti-tumor role through apoptosis pathway [48]In addition, IL7 can also enhance the anti-tumor immunity by combining other factors to enhance the function of immune cells (46).…”
Section: Discussionsupporting
confidence: 91%
“…aging-related genes(ARGs) play an important role in cell senescence and apoptosis. The expression of sense-cence genes can inhibit tumor cell proliferation and activate the body's speci c immune response by promoting tumor cell senescence and apoptosis, and promote the killing and elimination of tumor cells (5,10,11). However, the high expression of some ARGs can also inhibit tumor cell senescence and apoptosis (12,13).…”
mentioning
confidence: 99%
“…Mostly, these molecules are released during a certain time upon signal stimulation and the period of their action is most likely a reduced one, because of their limited life span in circulation [ 80 ]. Being part of the cytokine family, IL-1 family has been identified as a class of molecules, which mediate cellular communication within the immune system, possess multiple immunomodulatory functions, and participate in the regulation of tumor microenvironment [ 81 ]. Among them, IL-1 β and IL-18 are proinflammatory cytokines [ 82 ] and their actions during carcinogenesis development and progression will be further discussed.…”
Section: Molecular Inflammatory Events During Cancer Development Amentioning
confidence: 99%
“…Human interleukin-7 (IL-7) is a pleiotrophic cytokine with a wide range of immune effects, which exhibits a direct or indirect role in the anti-tumor effect; it can also affect the growth, survival, and differentiation of B and T cells ( 5 ). At present, IL-7 application in immunotherapy has entered the clinical trial phase and achieved certain curative effects, including the cases of melanoma, lymphoma, and colon cancer ( 6 8 ). To date, clinical data have consistently demonstrated that IL-7 co-expression can prolong the survival time of CAR-T cells and improve their ability to expand and kill tumors ( 9 ).…”
Section: Introductionmentioning
confidence: 99%